Identification of an Alternate Maxillary Apical Base Landmark from Pre-existing Substitution given by Different Authors - Patel, Kunal Patel; Parikh, Kartik; Singh, Varun Pratap; Soni, Jay (Orthodontic Journal of Nepal, 2014)
Introduction: It is often difficult to locate Point A in a lateral cephalogram due to operational errors. Faulty identification of PointA can lead to erroneous measurement and faulty diagnosis. Objective: To identify nearest alternative maxillary apical base landmark for Point A substitutions given by different authors. Materials & Method: A cross sectional study was conducted on thirty good quality lateral cephalograms, which were appraisedfor skeletal Class I with the help of parameters angle ANB, WITS appraisal and Beta angle. Only those lateral cephalogramswere selected where Point A was easily identified. Landmarks: Sella (S), Nasion (N), Point A and three substitution points Y, L, Xwere traced. Angles formed by SN with Point A (Angle SNA) and three substitution points (Angle SNY, SNX, SNL) were measured.Correlation of angle SNA with angles SNY, SNX and SNL were derived. Result: A mean value of 82.8o ±1.9o, 83.1o ±1.8o, 78.3o ±2.9o and 78.7o ±2.7o for Angle’s SNA, SNY, SNL and SNX respectivelywas observed. A statistically significant correlation was observed between angles SNA and SNY, SNL, SNX; and strong positivecorrelation was observed with angle SNY. Conclusion: Point Y is the most nearing maxillary apical base landmark to Point A. Hence maxillary apical base landmark canbe substituted by Point Y where identification of point A is not obvious.